UJI TOKSISITAS (Brine Shrimp Lethality Test) EKSTRAK DAN ISOLAT FRAKSI KLOROFORM DARI DAUN KEREHAU (Callicarpa longifolia Lamk.) - Arie Novadiana; Erwin -; Subur P Pasaribu (PROSIDING SEMINAR KIMIA, 2013)
Kerehau (Callicarpa longifolia Lamk.) is one of the biodiversity used as traditional medicine by one of the indigenous tribes of Borneo, called Dayak Tunjung. The purpose of this study was to determine about toxicity level of the Kerehau leaves (Callicarpa longifolia Lamk.) to larvae shrimps (Artemia Salina Leach) and to determine the content of the active compounds contained in the Kerehau leaves (Callicarpa longifolia Lamk.). The research was conducted by extracting samples with methanol and then concentrated by rotary evaporator. Total extract fractionated with n-hexane and chloroform, and then column chromatography applicated to chloroform fraction. Phytochemicals and BSLT have been test to Isolates chromatography results, total extract and chloroform extracts to determine the level of toxicity. Based on the results test of phytochemical compounds secondary metabolites of Kerehau leaves (Callicarpa longifolia Lamk.) indicated that the methanol extract containing steroid compounds, phenolics, and flavonoids. Chloroform fractions containing flavonoids and steroid compounds. Isolates Chloroform fraction containing Steroids compounds. On Brine Shrimp Lethality Test, death of larvae shrimps (Artemia Salina Leach) were recorded and processed using SAS Probit analysis to determine the value of Lethal Concentration (LC 50 ) to the value of each is, in chloroform isolates with LC 50 values of 96.4096 ppm, chloroform extract had LC 50 values of 104.1878 ppm and methanol extract had LC 50 values of 485.1681 ppm.